L'hermaphrodite et la bisexualité à l'épreuve du droit dans l'antiquité - Cantarella, Eva (Diogène, 2004)
Traduit de l’italien.
Keywords: LGBTQIA2+; androgynie; antiquité; approches et analyses; bisexualité; cours; discipline; discours dominant; europe; grèce; grèce antique; his4860; homosexualité; identités LGBTQIA2+; intersexuation; inégalités; moeurs sexuelles; mythologie; patriarcat; premier cycle; périodes historiques; rapports sociaux; rome antique; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (University of Minnesota Press, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; cours; discipline; discours dominant; fem1000; fem3300; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; queer of color; racisme; ressource en ligne; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; violences; états-unis